Forces on micron-sized particles randomly distributed on the surface of larger particles and possibility of detachment - Cui, Yan; Sommerfeld, Martin (International Journal of Multiphase Flow, 2015)
Numerical calculations based on the Lattice-Boltzmann method were performed for a particle cluster consisting of a large carrier particle covered with small spherical drug particles which were exposed to a constant velocity air flow. Prior to these studies, the simulations were validated based on a test case where a single particle is situated on a plane wall and exposed to a linear shear flow. The present simulations were compared with analytical results and other simulations. Moreover, the required small particle resolution and the domain size were properly selected based on an extensive numerical study. The diameter of the carrier particles was 100 μm, while the fine particles had diameters of 3 μm and 5 μm, respectively. The range of Reynolds numbers considered was between 1 and 200. Moreover, the coverage degree of the carrier by the small particles was varied in the simulations between 10% and 50%, and this influence on the detachment was determined. From these simulations the fluid dynamic forces on the drug particles were extracted in dependence of the angular position in order to estimate the possibility of drug particle detachment. Detachment might occur through lift-off, sliding or rolling. Lift-off was found to be not possible due to the acting small normal forces even at Re = 200. The probability of sliding and rolling detachment in dependence of the angular position was estimated based on measured adhesion properties, i.e. van der Waals force, adhesion surface energy and friction coefficient. With these studies it is aimed to understand drug particle detachment from carrier particles in an inhaler device as a basis of modelling and optimising dry powder inhalation.<br
Keywords: Carrier covered with drug powder; Dry powder inhaler; Carrier particles; Fluid forces on drug particles; Flow about the particle cluster; Probability of drug detachment; Lattice-Boltzmann Method